2016
DOI: 10.3945/ajcn.115.123414
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin-induced satiety is associated with gastrointestinal distress but not with the release of satiety hormones

Abstract: Background: Capsaicin, which is the major pungent principle in chili peppers, is able to induce satiety and reduce caloric intake. The exact mechanism behind this satiating effect is still unknown. We hypothesized that capsaicin induces satiety through the release of gastrointestinal peptides, such as glucagon-like peptide-1 (GLP-1) and peptide YY (PYY), from enteroendocrine cells in the small intestine. Objective: We investigate the effects of an intraduodenal capsaicin infusion (1.5 mg pure capsaicin) in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 40 publications
(47 reference statements)
2
39
0
Order By: Relevance
“…35 However, our results on gastrointestinal well-being are discordant with a previous study by van Avesaat et al on pungent spices using capsaicin as a regiment. 36 Their study showed that intra-duodenal capsaicin delivery affects satiety and gastrointestinal stress while it had no impact on postprandial PYY and GLP-1 release. 36 Thus, they inferred that the satiety-inducing mechanism of capsaicin may not be related to gut hormone secretion but to the perceived spiciness and gastrointestinal stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 However, our results on gastrointestinal well-being are discordant with a previous study by van Avesaat et al on pungent spices using capsaicin as a regiment. 36 Their study showed that intra-duodenal capsaicin delivery affects satiety and gastrointestinal stress while it had no impact on postprandial PYY and GLP-1 release. 36 Thus, they inferred that the satiety-inducing mechanism of capsaicin may not be related to gut hormone secretion but to the perceived spiciness and gastrointestinal stress.…”
Section: Discussionmentioning
confidence: 99%
“…36 Their study showed that intra-duodenal capsaicin delivery affects satiety and gastrointestinal stress while it had no impact on postprandial PYY and GLP-1 release. 36 Thus, they inferred that the satiety-inducing mechanism of capsaicin may not be related to gut hormone secretion but to the perceived spiciness and gastrointestinal stress. 36 We instead showed that neither the BPB nor the control beverage affected 'abdominal pain', 'stomach rumbling', 'flatulence', 'abdominal bloating', 'acid reflux', 'nausea' and 'urge to vomit' ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the expression patterns of TRPV1 in mice have demonstrated the channel's presence along the entire gastrointestinal tract . Although human studies are more scarce, the expression of TRPV1 in the oesophagus and colon is now well documented, and the channel is suspected to be present in the human small intestine as well . Immunostaining of human colon biopsies has demonstrated TRPV1‐positive fibres throughout the mucosa, with a particular abundance in the submucosal plexus .…”
Section: Trpv1mentioning
confidence: 99%
“…The best way to eat legumes would be to eat the whole grains (Earthman et al 2012). Not only is flax oil rich in omega-3 but it also is found to lower cholesterol (van Avesaat et al 2016).…”
Section: Vitamin Dmentioning
confidence: 99%